Comparative study of thermohydraulic performance in mini-channel heat sink systems: Multi-objective optimization and exergy considerations - Zouheyr Noui; Mohamed Si-Ameur; Nabil Bessanane; Amel Djebara; Adnan Ibrahim; Muhammad Amir Aziat Bin Ishak; Raheem K. Ajeel; Sharul Sham Dol (Case Studies in Thermal Engineering)
A numerical investigation is undertaken, employing a 3D conjugated heat transfer model to examine the impact of geometric configurations and hydrodynamical parameters on the overall thermal resistance and pumping power in mini-channels heat sinks. The aim lies in its holistic approach, integrating the non-uniform section of the mini-channel, the impact of the inlet velocity, the energy and exergy analysis, multi-objective optimization and performance evaluation criteria (PEC) evaluations, and the consideration of metal Galinstan and Cu-water nanofluid working fluids. The parametric analysis highlighted metal Galinstan as the best coolant for the five configurations involved in the present study. Furthermore, The PEC results indicate that the best performance is achieved by the Converged-Diverged Mini-channel (CDMC)heat sink. CDMC configuration with metal Galinstan performs well in terms of exergy evaluations and shows a better average temperature distribution with a maximum temperature of about 328K. The optimal inlet velocity (Uin = 0.21 m/s) is determined on the basis of the pumping power and thermal resistance profiles. The optimization process is based on the impact of the mini-channel's maximum width on the PEC. It is shown that the PEC increases with the maximum width of the CDMC and the highest (PEC = 1.31) is obtained at a maximum width of 0.95 mm.